Education on marine issues through marine debris cleanup and sampling activities - Siburian, Rima H. S.; Tapilatu, Julia Rosemary; Tapilatu, Maryrose E.; Wanggai, Marthenci I.; Ismayanti, Clara; S., Marlina; Yehezkiel, Boby (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
Marine debris is a problem caused by anthropogenic activities in land and sea, threatening the balance of marine ecosystems. Marine Debris Sampling and Volunteering activities are one of the actions organized by Our ConservaSea to increase public understanding about marine debris, as well providing overview of the status of marine debris in Manokwari coastal area. Activity was carried in 4 coastal locations in Manokwari at the end of 2022 to early 2023. Data collection was carried out descriptively. Based on the results of questionnaires and data of the program, we found out of 35 total participants, 91% rated the structure of the activity as very good, 82% answered that the activity facilities were very good, and 100% rated that the presentation of marine debris information had been delivered very well. Furthermore, the results of the activity content can reach up to 765 community engagement on social media.